2014
DOI: 10.1016/j.jpeds.2013.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Infection and Other Clinical Correlates of Abnormal Heart Rate Characteristics in Preterm Infants

Abstract: Objective Identify clinical conditions associated with a large increase (spike) in the heart rate characteristics index in VLBW infants. Study design Retrospective medical record review within a day of all large heart rate characteristics index spikes (increase of ≥3 from prior 5 day average) in VLBW infants at a single center enrolled from 2007–2010 in a multicenter trial of heart rate characteristics monitoring. In the trial, infants were randomized to having their heart rate characteristics index displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 23 publications
0
50
0
2
Order By: Relevance
“…Excluding cases of surgery, 53% of HRC index spikes were associated with suspected or proven infection (including urinary tract infection) or NEC. Thirty-four percent of the spikes were associated with acute respiratory deterioration without infection [40]. In some infants, there were increased apneic spells with associated heart rate decelerations but in other cases infants were on mechanical ventilation, in which case the abnormal heart rate characteristics may have been due to acute lung inflammation, respiratory acidosis, or hypoxemia.…”
Section: Challenges Associated With Hrc Index Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluding cases of surgery, 53% of HRC index spikes were associated with suspected or proven infection (including urinary tract infection) or NEC. Thirty-four percent of the spikes were associated with acute respiratory deterioration without infection [40]. In some infants, there were increased apneic spells with associated heart rate decelerations but in other cases infants were on mechanical ventilation, in which case the abnormal heart rate characteristics may have been due to acute lung inflammation, respiratory acidosis, or hypoxemia.…”
Section: Challenges Associated With Hrc Index Monitoringmentioning
confidence: 99%
“…For example, infants with grade III-IV intraventricular hemorrhage [41] and those with significant lung disease [40] may have a high score with frequent spikes for several weeks after birth (see Case 4). For infants with a chronically elevated HRC index, other clinical variables and laboratory tests must be used in decisions about obtaining cultures and administering antibiotics.…”
Section: Challenges Associated With Hrc Index Monitoringmentioning
confidence: 99%
“…7 In a site-specific analysis of patients enrolled in the RCT, 22% of patients with 'spikes', defined as sharp rises (>3) in the HRC index, developed necrotising enterocolitis or culture-positive infection (urine or blood). 8 Infants with spikes were more likely to have antimicrobial treatment initiated. In an editorial that accompanied the publication of the RCT, the authors asked "will the benefits transfer beyond the clinical trial environment in general neonatal practice?"…”
Section: Introductionmentioning
confidence: 99%
“…[84, 85*] In the multicenter randomized trial of visible results from heart rate characteristic monitoring vs. blinded data collection, 30 day mortality among infected infants was 10% among those with displayed heart rate characteristics, and 16% among controls (p = 0.01). Investigators also found that the number of sepsis work-ups and days of antibiotics total in both groups were similar.…”
Section: Antibiotic Practice Modifications/stewardship Effortsmentioning
confidence: 99%